The Making of Middle Class in Africa: Evidence from DHS Data - Mthuli Ncube; Abebe Shimeles (Institute for the Study of Labor (IZA), 2013)
This paper presents evidence on the making of the middle class in Africa by exploiting a comparable micro data from the Demographic and Health Surveys (DHS) for thirty-seven countries over two decades consisting of over seven hundred thousand household histories. We constructed a pseudo-panel to examine the dynamics of middle class in blocks of four periods covering the period 1990-2011. A key finding is that there was significant mobility of the middle class to the upper class in the last two decades with very few slipping back to poverty with obvious difference across countries. The paper approached the making of a middle class in Africa from institutional and policy perspectives. Initial conditions such as level of development in early decades, quality of institutions and most of all ethnic fractionalization play a significant role in determining the growth of the middle class in recent years. In addition we found evidence suggesting that the size of the middle class is higher in countries where mutual trust among citizens tends to be stronger. The role of education feature prominently in the making of the middle class. In about 30 of the 83 country-level regression decompositions we conducted for the asset index, the contribution of education exceeded 25% in explaining the overall variance in the asset index. The premium (or return) individuals obtain from achieving primary, secondary and tertiary level of education is unambiguously high compared with no education, but the effect decreases as the mean level of schooling increases.
Keywords: D31; J15; 330; middle class; asset index; multiple correspondence analysis; regression decomposition